Plyometric exercises to improve explosive power in artistic gymnastics - Damian, M.; Popescu, R.; Oltean, A.; Traicu, C.; Giurgiu, L. (Science, Movement & Health, 2014)
Preparing gymnasts is more severe due to more frequent change of code points, the major role in preparing athletes taking him coach, he was forced constantly to find the best means of improving working methods. Of all the biomotric training qualities, strength and power are the most crit cal for many sports. Sports with speed-power dominance is based on developing solid strength and power. Understanding the mechanics and physics of force training and incorporate their principles workout will boost the competitiveness of athletes.